A new species of Pleurothallis (Orchidaceae: Pleurothallidinae) from Valle del Cauca, Colombia and a note on the relationship between subsections Macrophyllae-Racemosae and Antenniferae - Wilson, Mark (2017)
A new species of Pleurothallis from subsection Macrophyllae-Racemosae is described from Valle del Cauca, Colombia. Morphological characteristics to distinguish this species from Pleurothallis bicornis, P. subreniformis and P. torrana are presented. The micromorphology of the lip of the new species was studied utilizing scanning electron microscopy. Labellar micromorphology is discussed in relation to putative pollination mechanisms.